Factors associated with male acceptance of modern contraceptive methods. A descriptive cross-sectional study in a peri-urban municipality - Judith A. Anaman-Torgbor; Mirialys Fiona Nana Ama Anaman; Elvis Reindolf Kale; Kennedy Diema Konlan (Contraception and Reproductive Medicine)
Abstract Background Male knowledge and acceptance of modern contraceptive use play a significant role in uptake. This study assessed the factors associated with male acceptance of modern contraceptive methods in Ho Municipality. Methods A cross-sectional study with a quantitative approach was employed. Systematic random sampling was used to select 503 participants from households with married men and women. A structured pre-tested questionnaire, including open-ended and closed-ended questions, was researcher assistant administered. Data analysis was conducted using STATA version 17. Results The majority of the respondents identified that contraceptives are used to prevent pregnancy (91.19%), and also identified the following as birth control commodities: birth control pills (64.94%), female condoms (15.71%), intrauterine devices - IUDs (4.79%), and implants (4.21%). Factors such as affordability, employment status, income, and access significantly influenced male acceptance of contraceptives. The study revealed that men (84.67%) agreed with their partner to use contraceptives after sexual intercourse while only 37% agreed to use contraceptives before sexual intercourse. Among those who did not accept the use of modern contraceptives, the reason provided was the fear of side effects (65.13%). Men who find modern contraceptives affordable were more likely to use them (AOR = 8.15; 95%CI:3.49–19.02; p-value < 0.001). Also, unemployed men were less likely to use modern contraceptives (AOR = 0.14; 95%CI:0.044–0.44; p-value = 0.001). Men with lower income (50–900 cedis average monthly income level) were less likely to use modern contraceptives (AOR = 0.28; 95%CI:0.07–1.02; p-value = 0.05). Conclusion Increasing interventions aimed at continuously reducing the cost of modern contraceptives is essential for improving male acceptance and the overall success of modern contraceptive use in other communities with low male involvement. The government, Healthcare agencies, community leaders, and family planning organizations should work together to actively intervene in lowering the cost of modern contraceptives to improve access by men.